Study Pressure Drop for Two-Phase Flow in a Large Diameter Tube (Journal of the College of Basic Education, 2019)
The aim of this study is to discover the deviation of two phase flow correlations. A comparsion was made between the expermital values of two-phase flow pressure drops data were obtained experimentally by Al-Jumaily (1999) by using air-water mixture in a horizontal tube of (132 mm) nominal diameter and a test section of (32 m) long at pressure and temperature close to atmospheric and those predicted by three correlations well-used in the literature, which show that the homogeneous model was the best